Perovskite type denitration catalyst as well as synthesis method and application thereof

By using molten titanium slag and other additives for molten salt synthesis, a perovskite denitrification catalyst with high activity and excellent selectivity is prepared, which solves the problems of complex traditional processes, high cost and poor selectivity, and achieves low-cost , Low-temperature denitrification effect of green technology.

CN119327475APending Publication Date: 2025-01-21ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411319005.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The synthesis process of traditional perovskite oxide catalysts is complex, has high cost, large process wastewater discharge, low material purity, poor catalytic product selectivity, and strong equipment corrosion, which limits its application in low-temperature flue gas treatment.

Method used

Using molten titanium slag as the main raw material, combined with calcium carbonate, lanthanum oxide, manganese dioxide and sodium carbonate as additives, the perovskite oxide denitration catalyst is prepared through the molten salt method, which reduces the reaction temperature and process complexity, improves material purity and Catalytic activity.

Benefits of technology

A low-cost, green process has been achieved to prepare perovskite denitration catalysts, which reduces wastewater emissions, improves the low-temperature activity and selectivity of the catalyst, and meets the needs of practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327475A_ABST
    Figure CN119327475A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite type denitration catalyst as well as a synthesis method and application thereof, and belongs to the technical field of environmental catalytic materials. According to the synthesis method disclosed by the invention, the molten titanium slag is taken as a main raw material, the calcium carbonate, the lanthanum oxide, the manganese dioxide and the sodium carbonate are taken as additives, the perovskite oxide denitration catalyst is prepared by adopting a molten salt method, the synthesized denitration catalyst has excellent low-temperature activity, the conversion rate of near 100% of nitric oxide can be obtained within the temperature range of 125-200 DEG C, and the denitration catalyst has good application prospects. The selectivity of the catalyst is greatly improved, and the catalyst has N2 selectivity of 90% or above at 125-175 DEG C, and can meet the actual application requirements. The problems that traditional perovskite oxide synthesis depends on a pure reagent, the technological process is complex and the cost is high, and existing perovskite catalyst synthesis from titanium-containing blast furnace slag is large in technological wastewater discharge, high in reaction temperature, large in corrosion to equipment, low in synthesized material purity, poor in catalytic product selectivity and the like are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental catalytic materials, and in particular to a perovskite-type denitration catalyst and a synthesis method and application thereof. Background Art

[0002] Ammonia selective catalytic reduction (NH3-SCR) is a common method for reducing nitrogen oxides (NO x ) emission method. Currently, the commercially available VW-Ti oxide catalyst can operate effectively in the temperature range of 300℃-400℃. Due to the high active temperature window, the SCR unit is usually located upstream of the dust collector and is easily blocked by particulate matter and poisoned by heavy metals. Flue gas below 300℃ usually needs to be reheated to meet the catalyst temperature window, which leads to a large amount of fuel consumption and NOx during the heating process. x and increased emissions of volatile organic compounds. Therefore, the development of catalysts with low-temperature activity has become a core issue in the field of NH3-SCR denitrification. In recent years, many studies have shown that perovskite oxides are one of the candidate materials with application potential, with advantages such as high activity and stability. However, the synthesis process of traditional perovskite oxides is long and costly. When multi-element doping is used, the process is complicated and impurity phases are easily formed. Therefore, finding a green and low-cost synthesis route is of profound significance for the widespread application of perovskite-type denitrification catalysts.

[0003] The invention patent with application number 202011634587.3 discloses a highly efficient responsive light-coupled denitration catalyst and a preparation method thereof, which mixes titanium-containing blast furnace slag powder, manganese oxide and NaOH, heats them up to a molten state in stages, and obtains a light-coupled low-temperature denitration catalyst by acid leaching after in-situ optimization and mineral phase reconstruction. However, the above process has significant disadvantages in the preparation of perovskite-type denitration catalysts. First, due to the low titanium content (18wt% to 25wt%) and high content of aluminosilicate phase in titanium-containing blast furnace slag, the material consumes a large amount of alkali and acid during the synthesis process, and discharges a large amount of chlorine-containing wastewater during the acid leaching process. Second, the perovskite material prepared by this method has low purity, and the content of impurities such as silicon, aluminum, magnesium and sodium in the perovskite in the material exceeds 7wt%, which significantly affects the catalytic activity of the material. Third, in order to enhance the catalytic activity of the material, the manganese doping amount can only be increased in the material, resulting in poor material selectivity. The N2 selectivity is less than 75% at 175°C, which greatly limits the application of the material in low-temperature flue gas treatment. Fourth, the pilot test found that due to the high content of aluminosilicate phase in the above system, after melting, a dense wrapping of manganese oxide and perovskite is formed, which greatly hinders the diffusion of oxygen in the air into the molten pool, so that manganese in the molten pool exists in a low-valent state and cannot be dissolved into the perovskite lattice. In order to solve the above problems, the molten pool has to be stirred with oxygen at 1500°C, which greatly increases the complexity of the process and equipment. Fifth, NaOH is used as a modifier in this method. In laboratory and pilot furnace tests, it was found that NaOH corroded the equipment severely and burned through the furnace several times. Sixth, a considerable part of the titanium in the titanium-containing blast furnace slag exists in the perovskite phase. The perovskite phase has a high melting point, and in-situ doping often requires a higher temperature (1500°C), which poses a challenge to the process equipment. The above disadvantages show that it is not suitable to prepare perovskite-type denitrification catalysts using titanium-containing blast furnace slag as raw material. Summary of the invention

[0004] In view of the above-mentioned problems, the present invention aims to provide a perovskite denitrification catalyst, a synthesis method and application thereof, using molten titanium slag as the main raw material, calcium carbonate, lanthanum oxide, manganese dioxide and sodium carbonate as additives, and adopting a molten salt method to prepare a perovskite oxide denitrification catalyst, which effectively solves the problems that the traditional perovskite oxide synthesis relies on pure reagents, the process flow is complicated, the cost is high, and the existing synthesis of perovskite catalysts from titanium-containing blast furnace slag has large process wastewater discharge, high reaction temperature, high corrosion to equipment, low purity of synthesized materials, and poor selectivity of catalytic products.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for synthesizing a perovskite-type denitration catalyst comprises the following steps:

[0007] S1: fully mix the molten titanium slag with calcium, lanthanum oxide, manganese dioxide and sodium carbonate powder, and press them into blocks or pellets;

[0008] S2: heating the block sample obtained in step S1 to 1200° C. to 1400° C., keeping the temperature for 0.5 h to 2 h, and then cooling to room temperature;

[0009] S3: crushing and grinding the calcined product obtained in step S2 into powder, and separating it by acid leaching to obtain perovskite oxide, i.e., perovskite-type denitration catalyst.

[0010] Preferably, the pressure for pressing into blocks or pelletizing in step S1 is 2-4 MPa.

[0011] Preferably, in step S1, the mass ratio of calcification to molten titanium slag is 0.9 to 1.3.

[0012] Preferably, in step S1, the mass ratio of lanthanum oxide to molten titanium slag is 0.2 to 0.4.

[0013] Preferably, in step S1, the mass ratio of manganese dioxide to molten titanium slag is 0.2 to 0.4.

[0014] Preferably, in step S1, the mass ratio of sodium carbonate to molten titanium slag is 0.1 to 0.2.

[0015] Preferably, the calcification material in step S1 includes any one of calcium carbonate, calcium oxide or calcium hydroxide.

[0016] Furthermore, the present invention also includes a perovskite-type denitration catalyst prepared by the synthesis method as described above.

[0017] Furthermore, the present invention also includes the use of the aforementioned perovskite-type denitration catalyst in the selective catalytic reduction of ammonia.

[0018] The beneficial effects of the present invention are as follows: compared with the prior art, the present invention has the following improvements:

[0019] 1. The synthesis of the perovskite-type denitrification catalyst in the present invention uses molten titanium slag as the main raw material. The molten titanium slag is a titanium-rich material smelted in an electric furnace, which contains a relatively high content of titanium and iron. In terms of mass fraction, the TiO2 content reaches 48% to 75%, the Fe2O3 content is 10% to 40%, and the sum of the contents of major impurity components, such as MgO, Al2O3, and SiO2 is less than 20%, which provides the possibility for the green and low-cost preparation of perovskite-type denitrification catalysts.

[0020] 2. In the present invention, the calcium content in the molten titanium slag is low, and then by controlling the amount of calcium carbonate added, the molten salt system is transformed from Na-Ca-Mg-Al-Si-O to Na-Mg-Al-Si-O system, thereby reducing the melting point of the entire molten salt and reducing the reaction temperature from 1500°C to 1200°C.

[0021] 3. In the present invention, lanthanum is introduced into the A position of perovskite to achieve charge balance with iron, stimulate the activity of iron, reduce the manganese content in the perovskite, reduce the number of Mn-O-Mn structures, and significantly improve the nitrogen selectivity of the catalyst. In addition, in the 400nm-800nm ​​band, compared with CTF_S and CT_HT, the denitrification catalyst synthesized in the present invention has a greatly improved visible light absorption capacity, indicating that the introduction of lanthanum into the A position of perovskite can greatly improve the visible light response capacity and quantum efficiency of the material.

[0022] 4. In the present invention, sodium carbonate is used as a flux. On the one hand, its high melting point slows down the corrosion of the alkali to the reaction equipment. On the other hand, sodium carbonate forms a Na-Mg-Al-Si-O low melting point molten salt system with impurities in the slag, thereby reducing the reaction temperature of the molten salt method.

[0023] 5. The denitration catalyst synthesized in the present invention has excellent low-temperature activity and can obtain a nitrogen oxide conversion rate of nearly 100% in the temperature range of 125°C to 200°C. The selectivity of the catalyst is also greatly improved, with a N2 selectivity of more than 90% at 125°C to 175°C, which can meet the actual application requirements.

[0024] 6. Compared with the pure reagent hydrothermal synthesis method, the cost of the synthesis method of the denitrification catalyst in the present invention is reduced by more than 50%; compared with the extraction of perovskite from titanium-containing blast furnace slag, the amount of alkali used in the synthesis method of the present invention is reduced by 70%, and the amount of acid used is reduced by 60% to extract the same amount of perovskite; under the condition of the same impurity concentration in the wastewater, the wastewater discharge is reduced by 80%, the reaction temperature is reduced from 1500°C to 1200°C, and the corrosiveness to the reaction equipment is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The synthetic flow chart of the perovskite-type denitration catalyst in the present invention.

[0026] Figure 2 The NO of the catalyst samples and MnO2 at different manganese doping amounts in Examples 1 to 3 of the present invention is shown in FIG. x Conversion rate results.

[0027] Figure 3 The N2 selectivity results of the catalyst samples and MnO2 at different manganese doping amounts in Examples 1 to 3 of the present invention are shown.

[0028] Figure 4 The results are a comparison of the activities of the catalyst samples in Examples 3 to 6 of the present invention.

[0029] Figure 5 The UV-visible spectra of the denitration catalyst prepared in Example 1 of the present invention are compared with those of Fe-doped CaTiO3 (CTF_S) and pure CaTiO3 (CT_HT).

[0030] Figure 6 The denitration activity and N2 selectivity results of a catalyst in a comparative example of the present invention are shown.

[0031] Figure 7 The XRD spectra of the denitration catalysts prepared in Comparative Examples 1 to 4 of the present invention and the denitration catalyst in Example 1 are shown. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0033] The present invention provides a method for synthesizing a perovskite-type denitration catalyst, using molten titanium slag as the main raw material, calcium carbonate (calcium carbonate can be replaced by calcium oxide and calcium hydroxide), lanthanum oxide, manganese dioxide and sodium carbonate as additives, and adopting a molten salt method to prepare a perovskite oxide denitration catalyst. The specific operation process is as shown in the attached figure. Figure 1 As shown, the following steps are included:

[0034] S1: fully mix the molten titanium slag with calcium carbonate (calcium carbonate can be replaced by calcium oxide or calcium hydroxide), lanthanum oxide, manganese dioxide and sodium carbonate powder, and press them into blocks or balls at a pressure of 2-4 MPa to inhibit the corrosion of alkali to the equipment;

[0035] Specifically, the main chemical composition of the molten titanium slag is shown in Table 1, and its SEM morphology and element distribution diagram are shown in the attached figure. Figure 1 As shown in a.

[0036] Table 1 Main chemical composition of smelted titanium slag

[0037]

[0038] It can be seen from Table 1 that the total content of silicon, aluminum and magnesium in the molten titanium slag is less than 20% (calculated as oxides). The low total content of silicon, aluminum and magnesium greatly reduces the amount of acid and alkali used and the amount of subsequent acid leaching wastewater.

[0039] More specifically, the mass ratio of calcium carbonate to molten titanium slag is 0.9-1.3, the mass ratio of lanthanum oxide to molten titanium slag is 0.2-0.4, the mass ratio of manganese dioxide to molten titanium slag is 0.2-0.4, and the mass ratio of sodium carbonate to molten titanium slag is 0.1-0.2.

[0040] S2: Put the block sample obtained in step S1 into a crucible, heat it to 1200℃~1400℃, keep it warm for 0.5h~2h, and then cool it to room temperature. The SEM morphology and EDS composition results of the molten salt after cooling are as shown in the attached figure. Figure 1 As shown in b;

[0041] S3: The calcined product obtained in step S2 is crushed and ground into powder, and separated by acid leaching to obtain perovskite oxide, i.e., perovskite-type denitrification catalyst. The TEM morphology and element surface distribution diagram of the catalyst are shown in the attached figure. Figure 1 As shown in c.

[0042] In summary, the flow chart of the synthesis method of the perovskite type denitration catalyst in the present invention is as shown in the attached figure. Figure 1 As shown in middle d.

[0043] Embodiment 1:

[0044] In Example 1, 10g of molten titanium slag is taken as an example. The molten titanium slag is crushed and ball-milled, and the molten titanium slag powder is obtained after passing through a 200-mesh sieve. 12g CaCO3, 2.2g La2O3, 3.0g MnO2 and 1.0g Na2CO3 are added and mixed evenly, and then pressed into a block sample under a pressure of 3MPa, and the pressure holding time is 5min. The block sample is heated to 1400℃ in an air atmosphere and kept warm for 1 hour. After the insulation is completed, the sample is cooled to room temperature with the furnace. The calcined product is ground and then acid-leached to obtain a perovskite-type denitrification catalyst, and the sample number is recorded as CLTFM2_S.

[0045] Embodiment 2:

[0046] In Example 2, 10g of molten titanium slag is taken as an example. The molten titanium slag is crushed and ball-milled, and then passed through a 200-mesh sieve to obtain molten titanium slag powder. 13g CaCO3, 2.2g La2O3, 4.0g MnO2 and 1.0g Na2CO3 are added and mixed evenly, and then pressed into a block sample at a pressure of 5MPa for 5min. The block sample is heated to 1400°C in an air atmosphere and kept warm for 1 hour. After the insulation is completed, the sample is cooled to room temperature with the furnace. The calcined product is ground and then acid-leached to obtain a perovskite-type denitrification catalyst, and the sample number is recorded as CLTFM 2.6 _S.

[0047] Embodiment three:

[0048] In Example 3, 10g of molten titanium slag is taken as an example. The molten titanium slag is crushed and ball-milled, and then passed through a 200-mesh sieve to obtain molten titanium slag powder. 10.8g CaCO3, 2.2g La2O3, 2.0g MnO2 and 1.0g Na2CO3 are added and mixed evenly. Then, the mixture is pressed into a block sample under a pressure of 3MPa for 5 minutes. The block sample is heated to 1400°C in an air atmosphere and kept warm for 1 hour. After the heat preservation is completed, the sample is cooled to room temperature with the furnace. The calcined product is ground and then acid-leached to obtain a perovskite-type denitrification catalyst, and the sample number is recorded as CLTFM 1.4 _S.

[0049] Embodiment 4:

[0050] In Example 4, 10g of molten titanium slag is taken as an example. The molten titanium slag is crushed and ball-milled, and the molten titanium slag powder is obtained after passing through a 200-mesh sieve. 10.8g CaCO3, 2.2g La2O3, 2.0g MnO2 and 1.0g Na2CO3 are added and mixed evenly. Then, the mixture is pressed into a block sample under a pressure of 5MPa for 5min. The block sample is heated to 1400°C in an air atmosphere and kept warm for 1 hour. After the heat preservation is completed, the sample is cooled to room temperature with the furnace. The calcined product is ground and then acid-leached to obtain a perovskite-type denitrification catalyst, and the sample number is recorded as CLTFM 1.4 _S1.

[0051] Embodiment five:

[0052] In Example 5, 10g of molten titanium slag is taken as an example. The molten titanium slag is crushed and ball-milled, and the molten titanium slag powder is obtained after passing through a 200-mesh sieve. 9g CaCO3, 2.2g La2O3, 2.0g MnO2 and 2.0g Na2CO3 are added and mixed evenly. Then, the mixture is pressed into a block sample under a pressure of 3MPa for 5min. The block sample is heated to 1400°C in an air atmosphere and kept warm for 1 hour. After the heat preservation is completed, the sample is cooled to room temperature with the furnace. The calcined product is ground and then acid-leached to obtain a perovskite-type denitrification catalyst, and the sample number is recorded as CLTFM 1.4 _S2.

[0053] Embodiment six:

[0054] In Example 6, 10g of molten titanium slag is taken as an example. The molten titanium slag is crushed and ball-milled, and then passed through a 200-mesh sieve to obtain molten titanium slag powder. 9g CaCO3, 4.0g La2O3, 2.0g MnO2 and 2.0g Na2CO3 are added and mixed evenly. Then, the mixture is pressed into a block sample under a pressure of 3MPa for 5 minutes. The block sample is heated to 1400°C in an air atmosphere and kept warm for 1 hour. After the heat preservation is completed, the sample is cooled to room temperature with the furnace. The calcined product is ground and then acid-leached to obtain a perovskite-type denitrification catalyst, and the sample number is recorded as CLTFM 1.4 _S3.

[0055] The perovskite denitration catalysts prepared in Examples 1 to 6 were used as a comparison with MnO2 to conduct a catalyst denitration activity experiment and a N2 selectivity experiment, specifically including the following contents:

[0056] The reaction device used in the present invention is a quartz reactor, and the quartz reactor is placed in a customized photothermal coupling denitrification reaction bed; the reaction device can be used to test the denitrification activity of the catalyst under dark field and visible light.

[0057] The flow rate of the reaction gas used in the present invention is 100 mL / min, and the NO gas concentration in the reaction gas is 500 ppm, the NH3 concentration is 500 ppm, the O2 concentration is 3 vol%, and nitrogen is the balance gas.

[0058] The specific experimental process is as follows: the reaction gas is introduced into the quartz reactor for 40 minutes, and then the catalyst is loaded into the quartz reactor and placed in the reaction bed for ventilation at room temperature for 1 hour. x After the concentration reaches a stable state, the temperature is raised and the xenon light source is turned on under photocatalytic conditions (preheating for 30 minutes in advance). The insulation temperatures are 50°C, 100°C, 125°C, 150°C, 175°C, and 200°C, respectively, the insulation time is 15 minutes, and the heating rate is 5°C / min.

[0059] Attached Figure 2 The NO of the catalyst samples and MnO2 at different manganese doping amounts in Examples 1 to 3 x Conversion rate, it can be seen that when the ratio of manganese is 1.4:15 (molar ratio of Mn to Ti+Fe+Mn), CLTFM 1.4 The NO conversion rate of CLTFM2_S increases with the increase of temperature, reaching 99.9% at 175℃. When the manganese ratio is increased to 2:15, CLTFM2_S obtains a NO conversion rate of nearly 100.0% at 150℃. When the manganese ratio is further increased to 2.6:15, CLTFM 2.6 _S reaches nearly 100.0% NO conversion at 125℃.

[0060] Attached Figure 3 The N2 selectivity of the catalyst samples and MnO2 at different manganese doping levels in Examples 1 to 3 is shown. It can be seen that the N2 selectivity of pure MnO2 decreases sharply with increasing temperature, and the selectivity is almost 0 at 200°C. Catalyst CLTFM 1.4 The N2 selectivity of _S changes the least, which is 95.8% at 200℃. When the manganese ratio is increased from 1.4:15 to 2:15 and 2.6:15, the selectivity decreases from 95.8% at 200℃ to 81.5% and 43.3%, respectively. The trend of the change of N2 selectivity of samples with manganese doping shows that the selectivity is negatively correlated with the manganese content. The Mn-O-Mn structure in perovskite is conducive to the formation of N2O, while the Mn-O-Ti structure can inhibit the formation of N2O.

[0061] Attached Figure 4 The results of the comparison of the catalyst activities in Examples 3 to 6 are shown in the attached figure. Figure 4 It can be seen that CLTFM 1.4 _S1, CLTFM 1.4 _S2 and CLTFM 1.4 _S3 Three samples with CLTFM 1.4 The activity of _S samples differed little.

[0062] In addition, the UV-visible spectra of the denitration catalyst prepared in Example 1 are compared with those of Fe-doped CaTiO3 (CTF_S) and pure CaTiO3 (CT_HT). Figure 5 As shown in the attached Figure 5 It can be seen that in the 400nm~800nm ​​band, compared with CTF_S and CT_HT, the denitrification catalyst CLTFM2_S synthesized in the present invention has greatly improved visible light absorption capacity, and lanthanum doping at the A position greatly improves the visible light response ability and quantum efficiency of the material.

[0063] Comparative Example 1:

[0064] In comparative example 1, 10 g of molten titanium slag, 9.2 g of CaCO3 and 1.0 g of NaOH were placed in an agate mortar and ground for more than 50 min to ensure that the sample was fully mixed. The powder mixture was made into a block sample under a pressure of 3 MPa. The block sample was placed in a crucible, placed in a muffle furnace, heated to 1400 ° C in an air atmosphere, and then kept warm for 1 hour. After cooling to room temperature, the calcined product was taken out, ground and acid-leached to obtain a denitration catalyst.

[0065] The denitrification activity and N2 selectivity of the catalyst are shown in the attached Figure 6 As shown in the attached Figure 6 It can be seen that the catalyst removes NO at 100℃-200℃x The efficiency can reach more than 30%, and the highest can reach 35.8%. The N2 selectivity is greater than 92.0% in the range of 50℃-200℃. Although the selectivity is good, the activity of the sample is poor. When the reaction temperature is 150℃, the NO conversion rate of the sample in comparative example 1 is 37.6%, which is much lower than 100% of the sample in Example 1, 100% of the sample in Example 2, and 72.7% of the sample in Example 3.

[0066] Comparative Example 2:

[0067] In comparative example 2, 10.0 g of molten titanium slag, 12.0 g of CaCO3, 2.2 g of La2O3, 3.0 g of MnO2 and 1.0 g of NaOH were placed in an agate mortar and ground and mixed for more than 50 min to ensure that the sample was fully mixed. The powder mixture was made into a block sample under a pressure of 3 MPa. The block sample was placed in a crucible, placed in a muffle furnace, heated to 600 ° C in an air atmosphere, and then kept warm for 1 hour. After cooling to room temperature, the calcined product was taken out, ground and acid-leached to obtain a denitration catalyst.

[0068] Comparative Example 3:

[0069] In comparative example 3, 10.0 g of molten titanium slag, 12.0 g of CaCO3, 2.2 g of La2O3, 3.0 g of MnO2 and 1.0 g of NaOH were placed in an agate mortar and ground and mixed for more than 50 min to ensure that the sample was fully mixed. The powder mixture was made into a block sample under a pressure of 3 MPa. The block sample was placed in a crucible, placed in a muffle furnace, heated to 900 ° C in an air atmosphere, and then kept warm for 1 hour. After cooling to room temperature, the calcined product was taken out, ground and acid-leached to obtain a denitration catalyst.

[0070] Comparative Example 4:

[0071] In comparative example 4, 10.0 g of molten titanium slag, 12.0 g of CaCO3, 2.2 g of La2O3, 3.0 g of MnO2 and 1.0 g of NaOH were placed in an agate mortar and ground and mixed for more than 50 min to ensure that the sample was fully mixed. The powder mixture was made into a block sample under a pressure of 3 MPa. The block sample was placed in a crucible, placed in a muffle furnace, heated to 1100 ° C in an air atmosphere, and then kept warm for 1 hour. After cooling to room temperature, the calcined product was taken out, ground and acid-leached to obtain a denitration catalyst.

[0072] The XRD spectra of the denitration catalysts prepared in Comparative Examples 1 to 4 and the denitration catalyst in Example 1 are shown in the attached figure. Figure 7 As shown in the attached Figure 7It can be seen that the denitration catalysts in Comparative Example 2 and Comparative Document 3 have almost no denitration activity, while the denitration catalyst in Comparative Example 4 has a certain denitration activity, with a denitration rate of only 23.2% at 150°C and an N2 selectivity of 100%. This is because at 1100°C, Na2Mn3O7 phase still remains in the calcined product, indicating that part of the manganese has not entered the perovskite phase, resulting in low yield and poor activity of the sample.

[0073] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for synthesizing a perovskite-type denitration catalyst, characterized in that: The following steps are involved: S1: fully mix the molten titanium slag with calcium, lanthanum oxide, manganese dioxide and sodium carbonate powder, and press them into blocks or pellets; S2: heating the block sample obtained in step S1 to 1200° C. to 1400° C., keeping the temperature for 0.5 h to 2 h, and then cooling to room temperature; S3: crushing and grinding the calcined product obtained in step S2 into powder, and separating it by acid leaching to obtain perovskite oxide, i.e., perovskite-type denitration catalyst.

2. The method for synthesizing a perovskite-type denitration catalyst according to claim 1, characterized in that: The pressure for pressing into blocks or pelletizing in step S1 is 2-4 MPa.

3. The method for synthesizing a perovskite-type denitration catalyst according to claim 1, characterized in that: In step S1, the mass ratio of calcification to molten titanium slag is 0.9 to 1.

3.

4. The method for synthesizing a perovskite-type denitration catalyst according to claim 1, characterized in that: In step S1, the mass ratio of lanthanum oxide to molten titanium slag is 0.2-0.

4.

5. The method for synthesizing a perovskite-type denitration catalyst according to claim 1, characterized in that: In step S1, the mass ratio of manganese dioxide to molten titanium slag is 0.2-0.

4.

6. The method for synthesizing a perovskite-type denitration catalyst according to claim 1, characterized in that: In step S1, the mass ratio of sodium carbonate to molten titanium slag is 0.1 to 0.

2.

7. The method for synthesizing a perovskite-type denitration catalyst according to claim 1, characterized in that: The calcified material in step S1 includes any one of calcium carbonate, calcium oxide or calcium hydroxide.

8. A perovskite-type denitration catalyst prepared by the synthesis method according to any one of claims 1 to 7.

9. Use of the perovskite-type denitration catalyst as claimed in claim 8 in the selective catalytic reduction of ammonia.

Citation Information

Patent Citations

  • Maeksumseok ceramic composition containing gold-coated maeksumseok and gold-coated titanium dioxide and manufacturing method thereof

    CN101838139A

  • Method for co-producing rutile by mineralizing CO2 from titanium-containing blast furnace slag

    CN113979472A

  • Method for preparing denitration and dioxin removal catalyst by using perovskite type composite oxide as carrier

    CN114308011A

  • Method for preparing ferrotitanium by using waste vanadium-tungsten-titanium catalyst

    CN116287716A

  • Nitrogen-doped perovskite catalyst and preparation method and application thereof

    CN117019200A